Die Schlaraffenlandkarte um 1700 Geografie und Ökonomie einer multimedialen Fantasie - Weder, Christine (Litterae, 2021)
Fascinating and enigmatic to this day: The Accurata Utopiae Tabula, an anonymous map of Cockaigne accompanied by an explanatory book (thought to be by Schnebelin), inspired the likes of Leibniz and was a popular supplement to atlases around 1700. Extensively embellished with euonyms for its locations, this multimedia ensemble offers a luxurious landscape of vices in addition to its 'merry discourse of gluttony and boozing'. The multilingual map contains hidden connections to not only fictional worlds, such as the lands of giants in Rabelais and Fischart, but also to such historical realities as the early modern economy of credit. An enjoyable journey of discovery across the borders of different arts and disciplines, guided by the compass of media history.